2019
DOI: 10.1021/acs.biomac.8b01712
|View full text |Cite
|
Sign up to set email alerts
|

Insights into siRNA Transfection in Suspension: Efficient Gene Silencing in Human Mesenchymal Stem Cells Encapsulated in Hyaluronic Acid Hydrogel

Abstract: Small interfering RNAs (siRNAs) are powerful tools for post-transcriptional gene silencing, which offers enormous opportunities for tissue engineering applications. However, poor serum stability, inefficient intracellular delivery, and inevitable toxicity of transfection reagents are the key barriers for their clinical translation. Thus, innovative strategies that allow safe and efficient intracellular delivery of the nucleic acid drugs at the desired site is urgently needed for a smooth clinical translation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…We have also recently demonstrated that this HA-mediated transfection method could be implemented in suspension cultures,p rovided the free HA is removed by centrifugation. [20] To ascertain the CD44 dependence of the siRNAuptake and gene KD,C D44-blocking studies were performed. [11] In these experiments,t he plated MG-63 cells were first incubated with low molecular weight HA (5 kDa) for 2hand the medium was then replenished with fresh medium containing 200 kDa HA (64 mm)and anti-GAPDH siRNA(200 nm).…”
mentioning
confidence: 99%
“…We have also recently demonstrated that this HA-mediated transfection method could be implemented in suspension cultures,p rovided the free HA is removed by centrifugation. [20] To ascertain the CD44 dependence of the siRNAuptake and gene KD,C D44-blocking studies were performed. [11] In these experiments,t he plated MG-63 cells were first incubated with low molecular weight HA (5 kDa) for 2hand the medium was then replenished with fresh medium containing 200 kDa HA (64 mm)and anti-GAPDH siRNA(200 nm).…”
mentioning
confidence: 99%
“…HA is known to play a significant role in cell proliferation and migration 26 and in maintaining the stem cell niche within our body. 27 Therefore hydrogels using HA components have been extensively used for several biomedical applications, such as cell delivery, 28 and drug delivery 29 and in the field of regenerative medicine. 30 We have previously developed a hydrazone-cross-linked HA hydrogel 29 and used it to deliver recombinant human bone morphogenetic protein-2 (rhBMP-2) to regenerate bone in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…30 We have previously developed a hydrazone-cross-linked HA hydrogel 29 and used it to deliver recombinant human bone morphogenetic protein-2 (rhBMP-2) to regenerate bone in vivo. 8,31 We have also utilized such materials to deliver small molecule drugs 32 and large nucleic acid drugs 28,33,34 and for tuning the differential release of proteins. 35 One of the key aspects of hydrogel preparation is the reaction kinetics of gel formation.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, aldehyde-modified hydrogels combined with acylhydrazide polyvinyl alcohol (PVA) can effectively deliver nontoxic siRNAs that can be applied to MSCs to block the inhibition of the clinically related gene PLEKHO1. is effect was demonstrated in siRNA release experiments and through the rheological properties of siRNA-encapsulated hydrogels [66].…”
Section: Aldehyde Modificationmentioning
confidence: 91%